Graphene oxide / sodium hydroxyl cellulose nano-composite film humidity sensor based on surface acoustic waves, preparation method and application
By using graphene oxide/hydroxycellulose sodium nanocomposite film as a sensitive material in the SAW humidity sensor, the problem of insufficient sensor response recovery speed and long-term stability is solved, and the effect of high sensitivity and rapid response is achieved.
Patent Information
- Application Number
- CN202510249122.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-04
- Publication Date
- 2025-05-02
AI Technical Summary
Existing surface acoustic wave (SAW) humidity sensors have shortcomings in response recovery speed and long-term stability, limiting their application potential in high-performance sensors.
A graphene oxide/hydroxycellulose sodium nanocomposite film was used as a sensitive material, and a uniform GO/CMC film was deposited on the surface of the SAW resonator by drop casting to prepare a high-performance SAW humidity sensor.
It achieves high sensitivity of 14.29kHz/%RH, fast response recovery time of 8s/12s and good long-term stability, which significantly improves the performance of the sensor.
Smart Images

Figure CN119915895A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of intelligent sensing, and relates to a surface acoustic wave (SAW) humidity sensor, and in particular to a surface acoustic wave-based graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor, a preparation method and an application thereof. Background Art
[0002] High-precision, fast-response humidity measurement plays a vital role in many fields, such as chemical manufacturing, aerospace technology, food storage, mineral mining, electronic product production, agriculture, and medicine. For example, in agriculture, plant growth and storage of fruits and vegetables have strict requirements on humidity; in the electronics industry, humidity control is crucial to the manufacturing and assembly process of optical components; in the medical field, humidity sensors are used to monitor environmental humidity to ensure the effectiveness of laboratory experiments, vaccine storage, and life support equipment; in the field of oil exploration, humidity sensors are also widely used in underground environment monitoring to ensure the normal operation of drilling equipment and the stability of the oil production process. Therefore, the development of high-performance, low-cost and sensitive humidity sensors is crucial for these applications.
[0003] At present, humidity sensors can be divided into many types according to different sensor mechanisms, including resistive, capacitive, optical fiber, colorimetric, quartz crystal microbalance and surface acoustic wave (SAW) humidity sensors. Among these sensors, surface acoustic wave sensors are favored by more and more scholars due to their small size, low cost, high sensitivity and linearity, wireless and passive characteristics. Compared with traditional active humidity sensors, they have low manufacturing cost, simple structure, good stability and long service life, so they are ideal for humidity detection and non-contact measurement in complex environments. Due to the outstanding advantages of SAW humidity sensors, researchers have carried out extensive research on it. Mittal et al. proposed a new type of fast sol-gel thin film porous metal oxide-based SAW humidity sensor. Compared with traditional commercial capacitive alumina sensors, the proposed sensor has a very fast response time (Tr = 1s) and excellent yield. The sensitivity (3%-20%RH) and hysteresis (3%-85%RH) are 120Hz / %RH and 0.3%, respectively. Lu et al. developed a SnO-based SAW humidity sensor. 2 / MoS 2 The high-performance SAW humidity sensor with nanocomposite as the sensitive layer and PMN-PT as the piezoelectric layer showed R 2Excellent linearity of >0.98 and high sensitivity of 0.78kHz / %RH and 8.87ppm / %RH, as well as low hysteresis, good repeatability and long-term stability, were achieved. However, the response / recovery time was too long, reaching 100s. Alam et al. fabricated three groups of sensors by changing the coating thickness of the polyvinyl alcohol (PVA) sensing film. The 5% PVA coated sensor had a maximum sensitivity of 3.72kHz / %RH for 0-30%RH and a response / recovery time of 35s / 40s. In addition, the sensor had a wide dynamic range. Wang et al. reported a GO humidity sensor based on surface acoustic waves, and finally formed a miniaturized integrated relative humidity sensing system of circuits and software. The system exhibited high sensitivity of 3.33kHz / %RH, fast response time of 80s and recovery time of 72s, good dynamic response and excellent repeatability. Su et al. proposed a three-dimensional structured graphene (3DAG) / polyvinyl alcohol (PVA) / SiO based on a quartz surface acoustic wave (SAW) delay block. 2 The humidity sensor layered sensing film is applied to respiratory monitoring. The sensor has a short response / recovery time (24s / 14.4s) and good stability, and has broad application prospects in clinical respiratory monitoring.
[0004] On the other hand, the sensitive material coated on the surface of the SAW device is one of the key factors that determine the sensing performance of the sensor. Choosing a suitable sensitive material can significantly improve the sensitivity and response recovery speed of the sensor. The sensing materials commonly used as the SAW sensitive layer include metal oxides, carbon-based materials and polymers. Graphene oxide (GO), as a derivative of carbon-based materials, has attracted widespread research interest in recent years because of its large specific surface area and rich oxygen-containing hydrophilic functional groups. However, sensors based on single graphene oxide usually face the problems of low sensitivity, slow response recovery speed and large errors after long-term use, which limits its application potential in high-performance sensors. Carboxymethyl cellulose (CMC) is a water-soluble cellulose derivative and a natural polymer material. Its molecular chain contains a large number of hydrophilic groups, such as -OH groups and -COONa groups, which makes it have strong hydrophilicity and good solubility and is widely used in humidity sensors. In order to eliminate the limitations of single GO materials in humidity response tests, different composite materials can be constructed according to the advantages of different materials to improve the performance of GO humidity sensors. Compared with single GO material, GO / CMC composite material not only has higher hydrophilicity and more stable humidity response performance, but also the introduction of CMC helps to improve the mechanical strength and conductivity of the material, and enhance the stability and reliability of the sensor in long-term use. Coating GO / CMC composite material on the surface of SAW device can further improve the performance of humidity sensor, especially in terms of improving response speed, enhancing sensitivity and improving long-term stability. So far, there has been no report of a GO / CMC humidity sensor based on surface acoustic wave. Summary of the invention
[0005] In view of this, the present invention discloses a graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic wave, a preparation method and an application thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The first technical purpose of the present invention is to provide a graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic wave, wherein the sensor is a SAW humidity sensor coated with a graphene oxide GO / sodium carboxymethyl cellulose CMC composite material, and is prepared by depositing a uniform GO / CMC film on the surface of a SAW resonator by a drop casting method.
[0008] The second technical purpose of the present invention is to provide a method for preparing the graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic wave as described above, the method specifically comprising the following steps:
[0009] The graphene oxide aqueous dispersion was mixed with anhydrous ethanol to form graphene oxide suspensions with concentrations of 0.1 mg / mL, 0.2 mg / mL, and 0.3 mg / mL, respectively;
[0010] Mixing carboxymethyl cellulose powder with deionized water to form carboxymethyl cellulose aqueous solutions with concentrations of 0.1 mg / mL, 0.2 mg / mL, and 0.3 mg / mL, respectively;
[0011] The prepared graphene oxide suspension is mixed with a carboxymethyl cellulose aqueous solution to form a mixed solution, which is drop-cast onto the resonator surface using a micropipette, and then the SAW resonator device coated with the sensitive material is dried to form a SAW sensor coated with a graphene oxide GO / sodium carboxymethyl cellulose CMC composite film.
[0012] It should be noted that the present invention has developed a SAW humidity sensor coated with GO / CMC composite material by drop casting. In order to compare the sensing performance, single GO and single CMC sensors were also synthesized for performance comparison. The GO / CMC composite nanomaterials were characterized by scanning electron microscopy (SEM). The prepared sensor was analyzed for humidity response in a wide humidity range at room temperature (25°C). Humidity sensing experiments showed that the GO / CMC sensor had an excellent sensitivity of 14.29kHz / %RH, a fast response / recovery time of 8s / 12s, and good long-term stability. This work shows the great potential of GO / CMC composites in humidity measurement of surface acoustic wave sensors.
[0013] Furthermore, at an ambient temperature of 25° C., the mixing ratio of the graphene oxide suspension and the carboxymethyl cellulose aqueous solution is (1-3): (1-3), preferably 1:1, 1:2, 1:3, 2:1, 3:1, and the drop casting volume of the mixed solution is 1 μL.
[0014] The third technical purpose of the present invention is to provide a graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic wave prepared by the method as described above, and its application in medical care, road transportation, environmental monitoring, and respiratory monitoring.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] The present invention deposits a uniform GO / CMC film on the surface of the SAW resonator by drop casting to prepare a GO / CMC surface acoustic wave sensor, which has an ultra-high sensitivity of 14.29kHz and a fast response recovery time of 8s / 12s in the humidity range of 11%-97%. At the same time, the sensor also has the advantages of good repeatability, low hysteresis, good long-term stability, etc., and has broad application prospects in the fields of medical care, road transportation, environmental monitoring, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0018] Figure 1 In the figure, (a) is a single-port resonator, (b) is a flow chart of GO / CMC sensor preparation, and (c) is a schematic diagram of a composite thin film sensor.
[0019] Figure 2 Humidity sensing system.
[0020] Figure 3 In the figure, (a) is the S11 parameter of the resonator without coating of GO / CMC film, and (b) is the S11 parameter of the sensor after coating of GO / CMC film.
[0021] Figure 4 In the figure, (a), (b), and (c) are the S11 response test diagrams of GO, CMC, and GO / CMC, (d) is the comparison of frequency offset tests of GO, CMC, and GO / CMC under different humidity conditions, (e) is the comparison of frequency offset of GO / CMC under different doping ratios and humidity conditions, and (f) is the full response test of the GO / CMC sensor.
[0022] Figure 5 In the figure, (a) is the comparison of response recovery time of GO, CMC, and GO / CMC sensors, (b) is the repeatability test of GO / CMC sensor, (c) is the hysteresis test of GO / CMC sensor, (d) is the long-term stability test of GO / CMC sensor, (e) is the frequency offset value test of GO / CMC at different room temperatures, and (f) is the selectivity test of GO / CMC sensor.
[0023] Figure 6 In the figure, (a) is the diagram of GO moisture absorption mechanism, and (b) is the diagram of GO / CMC moisture-sensitive performance improvement mechanism.
[0024] Figure 7 Among them, (a) is nasal breathing test, (b) is mouth breathing test, (c) is finger skin wetness test, and (d) is diaper leakage test. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.
[0027] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.
[0028] In the description of the present invention, it is necessary to understand that the terms "middle", "upper", "lower", "ascending", "descending", "vertical", "face", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0029] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.
[0030] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.
[0031] The invention discloses a graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic waves, a preparation method and an application thereof.
[0032] Example 1
[0033] A preparation method of a graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic wave is as follows:
[0034] 1) Materials
[0035] Graphene oxide aqueous dispersion (10 mg / mL) and carboxymethyl cellulose (purity 99.5%) were purchased from Aladdin Reagent (Shanghai) Co., Ltd., and deionized water was homemade in the laboratory. The single-port SAW resonator, with a resonant frequency of 315 MHz ± 75 kHz, was manufactured by Zhejiang Huayuan Microelectronics Technology Co., Ltd., China. Figure 1 (a) is shown. The piezoelectric substrate material of the SAW resonator is ST-cut quartz (size: 3.68mm×0.82mm×0.32mm). The manufacturing steps of the resonator are to clean the substrate and then deposit metal aluminum on the piezoelectric substrate by electron beam evaporation, and then use photolithography techniques such as exposure, development, etching, etc. to pattern the aluminum metal layer to form an aluminum electrode.
[0036] 2) Preparation of graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic wave
[0037] Take a certain amount of graphene oxide aqueous dispersion. Because anhydrous ethanol has good dispersibility and can make graphene oxide disperse more thoroughly, anhydrous ethanol is selected as the dispersant of graphene oxide. Mix the certain amount of graphene oxide aqueous dispersion with anhydrous ethanol in a beaker, stir for 60 minutes using a magnetic stirrer to form graphene oxide suspensions with concentrations of 0.1 mg / mL, 0.2 mg / mL, and 0.3 mg / mL, respectively. Then place the graphene oxide suspension in an ultrasonic cleaner and vibrate for 60 minutes to make the graphene oxide flakes smaller in size and more evenly distributed.
[0038] Then weigh a certain amount of carboxymethyl cellulose powder, mix the carboxymethyl cellulose powder with deionized water in a beaker, and stir with a magnetic stirrer for 30 minutes to form carboxymethyl cellulose aqueous solutions with concentrations of 0.1 mg / mL, 0.2 mg / mL, and 0.3 mg / mL, respectively. The prepared graphene oxide suspension and carboxymethyl cellulose aqueous solution were mixed according to the ratio of 1:1, 1:2, 1:3, 2:1, and 3:1 to form a mixed solution, and stirred with a magnetic stirrer for 30 minutes, and then 1 μL was drop-casted onto the resonator surface using a micropipette, and then the SAW resonator device coated with the sensitive material was placed in a drying oven at 60°C for 10 minutes to form SAW sensors with composite films of different proportions, such as Figure 1 As shown in (b) and (c).
[0039] 3) Sensor structure analysis and characterization
[0040] A variety of characterization techniques were used to analyze the SAW resonator device and the microstructure and elemental composition of the material in detail. First, the surface morphology of the IDTs and GO / CMC composites of the SAW resonator was characterized by scanning electron microscopy (SEM, Hitachi S-4800). The morphology and microstructure of the GO / CMC sensitive film were characterized by transmission electron microscopy (TEM, JEOL JEM-2100). Then, X-ray diffraction (XRD, Rigaku D / MAX-2550, Cu Kα radiation, ) studied the crystal structure of the material.
[0041] 4) Humidity sensing system
[0042] SAW humidity sensor measurement system Figure 2 The temperature in the laboratory was maintained at 25°C and the relative humidity was maintained at 25%RH. 3 COOK、MgCL 2 , K 2 CO 3 Mg(NO 3 ) 2 , CuCL 2 , NaCL, KCL, K 2 SO 4 The wide-mouth bottles with saturated solutions provide different relative humidity environments of 11%, 23%, 33%, 43%, 52%, 67%, 75%, 85% and 97%.
[0043] The SAW humidity sensor connection test fixture detects different humidity levels by quickly switching wide-mouth bottles with different humidity levels, and is connected to an external vector network analyzer (E5063A, Keysight, USA) through a SubMiniature version A (SMA) cable to observe changes in the resonant frequency in real time. The vector network analyzer is then connected to a PC via a network cable to record and export the measured data in real time.
[0044] Example 2-Example N
[0045] Based on the contents of Example 1 above, the technical solutions disclosed in Examples 2 to N differ from those in Example 1 only in that, in the process of preparing the sensor, GO / CMC sensors with different doping ratio parameters of 1:2, 1:3, 2:1, and 1:1 were prepared according to different solution concentrations, and the sensing performance was compared to select the optimal doping ratio parameter sensor for subsequent testing.
[0046] 1. Performance test of graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic wave
[0047] It should be noted that the SAW sensor used in the following performance test is specifically prepared according to Example 1.
[0048] The bare SAW device and the SAW sensor coated with 1 μL GO / CMC mixed solution were connected to a network analyzer to obtain the S11 parameters of the two devices, such as Figure 4 As shown. The resonant frequency of the bare SAW resonator is 314.915MHz, and the insertion loss is 11.07dB. After coating with GO / CMC film, the center frequency of the resonator increases to 315.3MHz, and the insertion loss increases by 10.19dB. The propagation process of surface acoustic waves is different from that of body waves (such as longitudinal waves and transverse waves). It only propagates along the solid surface, and its propagation characteristics are closely related to the surface and interface of the medium. For SAW humidity sensors, the change in the resonant frequency of the sensor is determined by formula (1):
[0049]
[0050] where f 0 is the resonant frequency of the sensor, λ is the wavelength of the surface acoustic wave, and v is the wave velocity of the surface acoustic wave. The wavelength of the surface acoustic wave is determined by the interdigital transducer structure of the resonator and is a constant. For the SAW humidity sensor, when the humidity changes and causes the resonant frequency of the sensor to change, the wavelength λ remains unchanged, so the resonant frequency change of the SAW humidity sensor is affected by the change in wave velocity. The surface of the SAW humidity sensor is usually covered with a layer of special sensitive materials that are highly reactive to environmental changes. When the sensor is exposed to the substance to be measured (such as moisture or gas), the sensitive material will undergo physical and chemical changes, and the adsorption of the substance to be measured will cause changes in its mass, conductivity, viscoelasticity and other properties. These changes will affect the propagation characteristics of the surface acoustic wave, thereby causing changes in the wave velocity, and ultimately causing the sensor resonant frequency to shift. Therefore, the change in wave velocity v is mainly caused by the mass load effect, the acoustoelectric effect and the viscoelastic effect, as shown in formula (2):
[0051]
[0052] In the formula, c m and c ε are the mass sensitivity coefficient and elastic coefficient of the piezoelectric substrate, m / A is the change in mass per unit area, and f 0 is the resonant frequency of the sensor, h is the coating film thickness, G is the real part of the shear modulus (storage modulus), K 2 is the electromechanical coupling coefficient of the sensor, σ 0 is the conductivity of the coated film, C 0 is the capacitance per unit length of the SAW substrate.
[0053] As the wave speed changes, the sensor resonant frequency f 0 The change is also caused by mass loading effect, acoustoelectric effect and viscoelastic effect
[38] The frequency change Δf is given by formula (3):
[0054]
[0055] The response (R) of the SAW humidity sensor is the change in the sensor's resonant frequency (Δf). The ratio of the change in resonant frequency to the change in relative humidity is defined as the sensitivity (S) of the SAW sensor, as shown in formula (4):
[0056]
[0057] Where |Δf| is the absolute value of the change in the resonant frequency of the SAW sensor, and ΔRH is the change in relative humidity.
[0058] The prepared GO, CMC, and GO / CMC humidity sensors were tested at 25°C in the detection range of 10% to 90% RH, and the waveforms and resonant frequencies under different relative humidity environments were obtained using a network analyzer.
[0059] We studied the response characteristics of GO, CMC and GO / CMC composite humidity sensors, especially the S11 response test with increasing humidity in the range of 11% to 97% relative humidity (RH). Figure 5 (a)(b)(c). The experimental results show that with the increase of relative humidity, the S11 response waveform of the sensor gradually shifts to the left. This phenomenon means that the resonant frequency of the sensor gradually decreases with the increase of humidity. This change in frequency reflects the influence of the change in material properties caused by humidity on the propagation characteristics of surface acoustic waves. Specifically, compared with GO sensors and CMC sensors, the waveform deviation of GO / CMC composite sensors is significantly more significant. With the increase of humidity, the S11 curve of the GO / CMC sensor shows a more obvious frequency change than that of a single material sensor.
[0060] The dynamic real-time response curves of the three sensors, GO, CMC and GO / CMC, at different humidity levels were tested. Figure 5(d) As shown. The relative humidity range is from 11% to 97% RH. As the relative humidity increases, the frequency of the sensor gradually increases. When the relative humidity reaches 97% RH, the frequency offset of the CMC sensor is 700kHz, the frequency offset of the GO sensor is 1100kHz, and the frequency offset of the GO / CMC sensor reaches 1660kHz. Calculated by formula (4), the sensitivity of the GO sensor in the test range is about 12.79kHz / %RH, the CMC sensor is about 8.14kHz / %RH, and the GO / CMC sensor is about 19.3kHz / %RH. The sensitivity of the GO / CMC sensor is about 1.5 times and 2.4 times that of the GO sensor and CMC sensor, respectively. This shows that under the same humidity conditions, the response of the GO / CMC composite sensor to humidity is much greater than that of the single CO and CMC sensors, indicating that the composite material greatly improves the performance of the sensor. In order to test the effect of different GO / CMC doping ratios on frequency shift, GO / CMC sensors with different doping ratios were prepared for frequency shift tests. The relationship between frequency shift (Δf) and relative humidity (x) was fitted using a power function. Under different doping ratios, the frequency shift showed a nonlinear upward trend with the increase of relative humidity, as shown in Figure 2. Figure 5 (e) The fitting curve equations of different doping ratios 1:2, 1:3, 2:1, 1:1 are Y=0.51949X 1.75079 ,Y=0.0222X 2.35165 , Y=0.15449X 1.95365 , Y=0.29612X 1.84608 , correlation coefficient (R 2 ) are 0.99593, 0.98457, 0.99876, and 0.9979, respectively. It can be seen from the fitting curve that in the range of 11% to 97% RH, when the GO / CMC doping ratio is 1:2, a larger frequency shift will be produced under the same humidity conditions. Figure 5 (f) is the full frequency response of the GO / CMC humidity sensor with a doping ratio of 1:2 in the range of 11% to 97% RH. As the relative humidity increases, the resonant frequency of the sensor decreases from 315.55 MHz at 11% RH to 313.9 MHz at 97% RH.
[0061] Response recovery time is also one of the important indicators for evaluating sensor performance. For SAW sensors, the response time is usually defined as the time required for the frequency offset to reach 90% of the maximum value, and the recovery time is defined as the time required for the frequency offset to decrease from the saturation state to 10% of the maximum value. Figure 6As shown in (a), in the range of 11% to 85% RH, the GO / CMC humidity sensor has a higher frequency offset and a shorter response recovery time than the GO and CMC humidity sensors. The response time of GO / CMC is 8s, which is approximately 2 / 7 and 1 / 8 of the response time of GO and CMC, respectively, and the recovery time of GO / CMC is 12s, which is approximately 1 / 3 and 1 / 4 of the recovery time of GO and CMC, respectively. It can be seen that the composite GO / CMC humidity sensor not only has a larger frequency response, but also has a great advantage in response recovery time compared to single GO and CMC sensors. Figure 6 (b) The test on the repeatability of GO / CMC is shown. The sensor was tested three times in three humidity environments: 33% RH, 52% RH, and 85% RH. It can be seen that in different humidity environments, the frequency offset curves of the sensor are very similar, and there are no abnormal phenomena such as inconsistent response and incomplete recovery. This shows that the GO / CMC humidity sensor has good repeatability.
[0062] Hysteresis is one of the important indicators for evaluating sensor performance. The sensor is tested for adsorption and desorption in the range of 11% to 97% RH. Figure 6 (c) As shown in Figure 3, during the desorption process, the frequency decreases with the change of humidity compared to the adsorption process, and the maximum frequency offset difference between adsorption and desorption accounts for about 2% of the total offset, so the sensor has low hysteresis. Figure 6 (d) shows the 30-day long-term stability of the GO / CMC sensor in three humidity environments: 33% RH, 52% RH, and 75% RHs. After 30 days of testing, the frequency response error of the sensor did not exceed 0.04MHz, indicating that the sensor has good long-term stability and has broad prospects in practical applications. The room temperature was always kept at 25°C during the test, but the ambient temperature will change continuously in actual application scenarios. Therefore, in order to explore the effect of ambient temperature on the sensor response, the ambient temperature was changed to test the frequency offset of the sensor under different humidity conditions, such as Figure 6 As shown in (e), the sensor was tested at 25℃, 30℃, and 35℃ respectively. Under the same humidity environment, the frequency offset values of the sensor are almost the same for different temperatures, indicating that the sensor can work normally at different room temperatures.
[0063] In many practical application scenarios, such as petrochemical plants, there will be many other gases that interfere with the sensor's measurement. Therefore, we selected four common industrial gases to test the sensor's anti-interference performance, such as Figure 6 As shown in (f), 50 ppm of H 2 S, CH 4 、SO 2 、NO 2The sensor was tested for frequency offset and compared with the frequency offset in 43% RH and 85% RH environments. It was found that the frequency offset values for the four gases were 11.21kHz, 9.86kHz, 5.62kHz, and 4.88kHz, respectively, which were less than 1% of the frequency offset value generated by the sensor from 11% to 85% RH, proving that the GO / CMC humidity sensor has good humidity selectivity.
[0064] The comparison between the GO / CMC SAW humidity sensor and the previously reported SAW humidity sensor is shown in Table 1. Previously reported SAW sensors mostly use delay linear SAW devices to prepare sensors, while the present invention uses resonator type SAW devices to prepare sensors. Resonator type SAW sensors have higher sensitivity than delay linear SAW sensors because the sensitive material is directly coated on the fork finger transducer. Delay line type SAW humidity sensors usually reflect humidity changes through changes in propagation delay, and their sensitivity is low. In addition, due to the characteristics of the working principle, the response time of resonator type SAW humidity sensors is usually short. Changes in humidity can be quickly reflected in frequency, and the response is faster. Delay line type SAW sensors usually have a slow response time because they rely on the propagation delay of sound waves. At the same time, compared with previously reported materials, GO / CMC composite materials have a very large relative specific surface area and defect sites, which can better adsorb moisture.
[0065] It can be seen from this that the GO / CMC SAW humidity sensor proposed in the present invention not only has higher sensitivity than most reported SAW humidity sensors, but also has a shorter response recovery time, demonstrating the superiority of the sensor of the present invention.
[0066] Table 1 Comparison of the sensing characteristics of SAW humidity sensors with those reported in the literature
[0067]
[0068] Note: The literature cited in Table 1 above is as follows:
[0069] [1]XHLe,
[0070] [2]F.Wang,J.M.Jian,X.S.Geng,G.Y.Gou,W.P.Cui,Y.C.Qiao,J.Fu,Y.Yang,T.L.Ren,A miniaturized integrated SAW sensing system for relative humiditybased on graphene oxide film,IEEE Sens.J.20(2020)9733-9739.
[0071] [3]F.Zheng,M.J.Li,C.P.Li,B.Z.Zhou,X.W.,Xuan,H.J.Li,Wireless surfaceacoustic wave humidity sensor with chitosan / porous cyclodextrin-TiO 2 composites for monitoring air and human respiration,Sens.Actuators BChem.379(2023)133235.
[0072] [4]L.Lu,J.Liu,Q.Li,Z.R.Yi,J.Q.Liu,X.L.Wang,X.Chen,B.Yang,Highperformance SnO 2 / MoS 2 -based surface acoustic wave humidity sensor with goodlinearity,IEEE Sens.J.,19(2019)11027-11033.
[0073] [5]Y.P.Su,C.P.Li,M.J.Li,H.J.Li,S.Xu,L.R.Qian,B.H.Yang,Surfaceacoustic wave humidity sensor based on three-dimensional architecturegraphene / PVA / SiO 2 and its application for respiration monitoring,Sens.Actuators B Chem.308(2020)127693.
[0074] 2. Analysis of the sensing mechanism of graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic wave
[0075] Simple graphene oxide (GO) humidity sensors usually show a slow response recovery speed, such as Figure 6 (a) As shown. Although the layered structure of GO has abundant surface defect sites (such as oxidized groups) that can adsorb water molecules, the interlayer distance is relatively small, resulting in water molecules not only staying on the defect sites on the GO surface, but also penetrating into the deep regions of the GO layer, such as Figure 6 (a) As shown. Due to the narrow interlayer spacing of GO, the penetration and diffusion of water molecules between these layers are slow. This tight layered structure makes it difficult for water molecules to desorb quickly, resulting in a long recovery time for the sensor. Therefore, the recovery time of the GO humidity sensor is long, affecting its real-time and accuracy in practical applications.
[0076] However, by adding carboxymethyl cellulose (CMC) to compound with GO, the sensitivity of humidity sensor can be significantly improved and its response recovery time can be shortened. CMC itself has good hydrophilicity. The molecular structure of CMC contains abundant hydroxyl groups and other polar groups, which can effectively interact with the defect sites on the surface of GO, enhance the adsorption capacity of water molecules, and improve the sensitivity of the sensor. In addition, the addition of CMC provides a supporting structure, such as Figure 6 As shown in (b), it can play a certain role in dispersing between GO layers and improve the interlayer spacing of GO. Through this physical effect, CMC makes the interlayer structure of GO no longer too tight, thereby increasing the permeability of water molecules between the layers. Water molecules are more likely to diffuse between GO layers, and the speed of adsorption and desorption is accelerated.
[0077] As shown in Equation 2, the main factors affecting SAW sensors are mass loading effect, acoustoelectric effect and viscoelastic effect. The resonant frequency of GO / CMC sensor decreases with the increase of humidity, and the main factor is mass loading effect. Figure 5As shown in (e), as the number of water molecules absorbed by the sensitive film increases and the mass of the load increases, the shift of the resonant frequency increases nonlinearly. The more water the sensitive film absorbs, the greater the frequency shift caused. The viscoelastic effect is another factor that causes the frequency shift due to moisture absorption. Due to the characteristics of its nanosheet structure, the graphene oxide layer has a higher shear modulus, which makes it have a stronger internal binding force than polymer materials. Therefore, in the GO / CMC film, the viscoelastic effect has a relatively small effect on the sensor performance. The adsorption of water molecules will cause changes in the conductivity of the sensitive layer, which in turn may affect the wave velocity and attenuation characteristics of the surface acoustic wave sensor. However, compared with some traditional polymer materials, the conductivity of the GO / CMC film changes less. Graphene oxide (GO) has strong conductivity, and its composite material with carboxymethyl cellulose (CMC) exhibits more stable conductivity properties. In addition, the effect of conductivity is usually only significant when the conductivity is within a specific conduction window. Within the conduction window, changes in conductivity have a significant effect on the wave velocity. However, if the initial conductivity of the sensor is not within this window, then the effect of changes in conductivity on the wave velocity is more limited.
[0078] 3. Application test of graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic wave
[0079] The application of SAW sensors in human breathing detection was studied. In order to detect the breathing condition of the human body, the SAW sensor was placed 3 cm away from the nasal cavity and 5 cm away from the mouth for breathing tests. The results are as follows: Figure 7 As shown in (a) and (b), the moisture brought out by the exhaled gas causes the sensor frequency to shift, and the frequency shift caused by mouth breathing is significantly greater than that caused by nasal breathing, about 0.3MHz, while nasal breathing is about 0.2MHz. At the same time, in order to test the application of SAW sensors in human skin humidity detection, the dry index finger and the wet index finger were placed 3 mm above the SAW sensor for testing. At the same time, the wet index finger moved left and right, staying above the sensor for 8 seconds each time. The results are shown in Figure 7 As shown in (c), the dry index finger does not affect the frequency of the sensor, while the evaporation of water on the wet index finger causes the sensor frequency to shift downward. When the wet index finger is removed, the sensor frequency shift will return to the initial state. For infants and some elderly people, diapers are a necessity in life, so the application of SAW sensors in detecting diaper leakage is also studied. The results are shown in Figure 7As shown in (d), the SAW sensor is placed on the diaper with its front side facing the surface. When the diaper surface is dry, the sensor frequency is normal. Water is poured into the diaper until water overflows to simulate leakage. At this time, the sensor frequency shifts by about 0.8MHz due to the change in humidity environment caused by water evaporation. This shows that SAW humidity sensors have the characteristics of wide application.
[0080] Based on the above analysis, this paper discloses a SAW humidity sensor based on GO / CMC, and characterizes and tests its humidity-sensitive performance. The GO / CMC mixed solution was deposited on the surface of the SAW device by drop casting to prepare a GO / CMC sensor. The SAW humidity sensor based on GO / CMC has a high sensitivity of 14.29kHz and a fast response recovery time of 8s / 12s, as well as low hysteresis and good repeatability and stability. In addition, the humidity-sensitive mechanism of the sensor is that the rich defect sites and functional groups of GO / CMC absorb a large amount of moisture, and the addition of CMC provides a supporting structure for rapid adsorption / desorption of moisture. The present invention provides a new nanocomposite design for the application of SAW humidity sensors, which has broad application prospects in the fields of health care, road transportation, and environmental monitoring.
[0081] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic wave, characterized in that: The sensor is a SAW humidity sensor coated with a graphene oxide GO / sodium carboxymethyl cellulose CMC composite material, which is prepared by depositing a uniform GO / CMC film on the surface of a SAW resonator by a drop casting method.
2. A method for preparing a surface acoustic wave-based graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor according to claim 1, characterized in that: Specific operations: mixing the graphene oxide aqueous dispersion with anhydrous ethanol to obtain a graphene oxide suspension; mixing carboxymethyl cellulose powder with deionized water to obtain a carboxymethyl cellulose aqueous solution; The prepared graphene oxide suspension is mixed with a carboxymethyl cellulose aqueous solution to form a mixed solution, which is drop-cast onto the resonator surface using a micropipette, and then the SAW resonator device coated with the sensitive material is dried to form a SAW sensor coated with a graphene oxide GO / sodium carboxymethyl cellulose CMC composite film.
3. The preparation method according to claim 2, characterized in that: At an ambient temperature of 25° C., the mixing ratio of the graphene oxide suspension and the carboxymethyl cellulose aqueous solution is (1-3): (1-3), and the drop casting volume of the mixed solution is 1 μL.
4. The preparation method according to claim 2, characterized in that: The concentration of the graphene oxide suspension is 0.1-0.3 mg / mL, and the concentration of the carboxymethyl cellulose aqueous solution is 0.1-0.3 mg / mL.
5. The preparation method according to claim 4, characterized in that: The concentration of the graphene oxide suspension is 0.1 mg / mL, 0.2 mg / mL, and 0.3 mg / mL, and the concentration of the carboxymethyl cellulose aqueous solution is 0.1 mg / mL, 0.2 mg / mL, and 0.3 mg / mL.
6. An application of the graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic wave as claimed in claim 1 or the graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic wave prepared by the method as claimed in claim 2 in medical care.
7. An application of the graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic wave as claimed in claim 1 or the graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic wave prepared by the method as claimed in claim 2 in road transportation.
8. Use of the graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic wave according to claim 1 or the graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic wave prepared by the method according to claim 2 in environmental monitoring.
9. Use of the graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic wave according to claim 1 or the graphene oxide / sodium hydroxycellulose nanocomposite film humidity sensor based on surface acoustic wave prepared by the method according to claim 2 in respiratory monitoring.